Pengaruh Earnings Management Terhadap Stock Return Dengan Earnings Quality Sebagai Variabel Intervening - Silvia Veronica Sugiarto; Devie Deviesa (Business Accounting Review, 2017)
Financial statements prepared by management may reflect whether the company financial condition is good or bad. Information on the company's financial condition is very important for external parties as a form of corporate accountability. Nowadays, there are many methods that can be used by management to manage the company's financial statements. Those earnings management actions would affect stock return for the investors. Therefore, this study intended to know whether the earnings management influenced on stock return.The sample of this study was LQ 45 companies that listed in Indonesian Stock Exchange in period 2012-2015. The data – processing method was done by validity, reliability, and statistic descriptive analysis. While the data analysis method used SPSS and Smart PLS 2.0 software. The result revealed that, earnings management influenced significantly and negatively on stock return directly, and indirectly through the intervening earnings quality variable.